HERBAL MEDICINAL PLANTS OF RAJASHTHAN :MUSLI: Life Science-Ethno botany - SHARMA, SANTOSH; KUMAR, ASHWANI (International Journal of Life Science and Pharma Research, 2012)
Now the traditional Indian system of medicine can be broadly classified into the empirical forms of folk medicine which are village based, region-specific, indigenous herb based, local resources based and in many cases, community-specific. The other system called the Shastriya stream which includes the Ayurveda, Siddha and Yunani systems of medicine is more complicated and elaborate with theoretical and research findings. Musli is useful as aphrodiasic and nervine tonic. Tribal uses of plant are presented here